2023
DOI: 10.1021/acs.chemmater.2c03645
|View full text |Cite
|
Sign up to set email alerts
|

Design of Olefin-Phobic Zeolites for Efficient Ethane and Ethylene Separation

Abstract: Selective adsorption of ethane from a mixture of ethane (C 2 H 6 ) and ethylene (C 2 H 4 ) has emerged as an energy-efficient process for obtaining high-purity ethylene. Recently, it has been reported that some novel microporous organometallic and organic adsorbents can preferentially adsorb C 2 H 6 over C 2 H 4 . Conversely, zeolite adsorbents, which are widely used in industry due to their high stability and low material cost, generally prefer C 2 H 4 adsorption ("olefin-philic"). In this study, we carefully… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“… a Group I comprises several pure-silica zeolites that are typically synthesized hydrothermally in the fluoride media, as reported in the literature. , Group II contains pure-silica zeolites that can be hydrothermally synthesized in the alkaline media. b Abbreviations of OSDAs utilized in this study, along with their corresponding structural formulas, can be found in the Supporting Information. c Si-SOD is used as the sole silica source. …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… a Group I comprises several pure-silica zeolites that are typically synthesized hydrothermally in the fluoride media, as reported in the literature. , Group II contains pure-silica zeolites that can be hydrothermally synthesized in the alkaline media. b Abbreviations of OSDAs utilized in this study, along with their corresponding structural formulas, can be found in the Supporting Information. c Si-SOD is used as the sole silica source. …”
Section: Resultsmentioning
confidence: 99%
“… a Group I comprises several pure-silica zeolites that are typically synthesized hydrothermally in the fluoride media, as reported in the literature. , Group II contains pure-silica zeolites that can be hydrothermally synthesized in the alkaline media. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…71,79 A similar mechanism involving the interaction of H in alkane C–H bonds with O in siloxane bridges have been proposed to drive the selective adsorption of ethane over ethylene on defect-free, purely-siliceous zeolites. 80 Also, unexpected isotope exchange of oxygen ( 17 O) into zeolite frameworks via equilibration of the zeolite with 17 O enriched water at room temperature 81–83 could be explained by a similar hydrogen bonding mechanism. H-Bonding of the isotope-enriched water to the siloxane bridges could assist in the reversible opening and closure of the siloxane bridges, thus enabling the exchange of framework 16 O with 17 O from water.…”
Section: Adsorption Mechanismmentioning
confidence: 99%